Crowdfunding Platform for Social Activities Using Blockchain - G. Shanmuga Priya (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Collecting funds for social activities is a challenging task, requiring the identification of the right places and organizations to meet the need. One of the major areas requiring substantial funding is the eradication of poverty, which is the first Sustainable Development Goal (SDG). Poverty remains a persistent global challenge, impacting millions. While traditional charities and development organizations play a crucial role, innovative solutions are needed to accelerate progress. Crowdfunding emerges as a promising avenue for fundraising. Crowdfunding leverages cutting-edge technology, particularly blockchain, to enhance the efficiency, secure, and transparent fundraising procedure. Blockchain technology a decentralized and distributed ledger system. Unlike traditional crowdfunding, where a centralized platform controls and monitors the fundraising procedure, decentralized blockchain crowdfunding platforms have no single point of control. This significantly reduces the risks of censorship and fraud. While crowdfunding has benefited many over the years, it has also witnessed significant scams. The proposed solution aims to build confidence among contributors to all causes by providing transparency to the crowdfunding process. All campaign, donation, withdrawal, and fund information would be stored on the network, accessible to everyone in a decentralized manner. This approach prevents data being centralized on a single server, ensuring that funds and transactions are visible and maintained at every node on the blockchain. This not only safeguards the funds from falling into the wrong hands but also ensures that they are utilized for the economic development of society.